A Review on Cardiovascular Disease Global Health Indicators, Cause Specific Risk Factors, and Quality of life Indicators - MARY, ANNAPOORNA (International Journal of Medical Research, 2013)
Background: Although there are many modifiable risk factors attributed to the cardiovascular diseases, which are amenable for prevention, cardiovascular diseases continue to remain a leading cause of mortality all over the world. Prevalence of global health disparity in primary, secondary, and tertiary levels of care for patients with cardiovascular disease conditions is a known phenomenon. However, the prevalence of global cause specific disparity among modifiable risk factors related to cardiovascular disease is unknown. The association between the Quality of life indicators and cause specific risk factors is unknown among heart disease patients. Identifying the association between risk factors and quality of life among heart disease patients may help to improve the recovery, rehabilitation, and quality of life. Purpose: The purpose of this review is to describe the cardiovascular health indicators and cause specific risk factors, and quality of life among patients with heart diseases. Method: A review included the published clinical research studies and systematic reviews from PUBMED. The concepts for the search included heart diseases risk factors, heart disease indicators, and quality of life after heart disease. The review was organized under method and results section of this article. Conclusion: The review laid foundation for a theoretical framework, containing definitions of the concepts and supporting evidences, that has been organized under the conceptual headings of the review including global disparity in CVD mortality, cardiovascular disease indicators and risk factors, individual risk factors, environmental risk factors, behavioral risk factors, demographic risk factors, summary measures of health indicators, quality indicators, and quality of life indicators.